Continuous and Discrete Deformation Modes of Mechanical Metamaterials With Ring-Like Unit Cells - Yang, Nan; Zhuang, Juncheng; Wei, Shichuan; Yu, Ying (Frontiers in Physics, 2022)
Structures with multiple deformation paths provide a promising platform for robotics, reprogrammable mechanical and thermal deformation materials, and so on. Reconfigurations with multi-path can fulfill many tasks (e.g., walking and grasping) and possess multiple properties (e.g., targeted Poisson’s ratio and thermal expansion coefficient). Here we propose a new ring-like kirigami structure, and theoretically and experimentally find that for a basic unit, there are four discrete deformation patterns and a continuous shearing deformation pattern; thus, there are a large number of discrete deformation patterns for a multi-unit combination with geometrical compatibility coupled with a shearing deformation mode. Moreover, targeted Poisson’s ratios (either + or -) in the x- and y-directions can be realized by inversely designing the geometrical parameters for certain deformation path. Additionally, we show the capability of constructing 2D and 3D cellular structures in various patterns with the proposed ring-like units. The multiple deformation modes demonstrated here open up avenues to design new reprogrammable materials and robots across various scales.